Submerged cage aquaculture of marine fish: A review of the biological challenges and opportunities. (22nd June 2021) - Sievers, Michael; Korsøen, Øyvind; Warren‐Myers, Fletcher; Oppedal, Frode; Macaulay, Georgia; Folkedal, Ole; Dempster, Tim
Abstract: Surface‐based cages are the dominant production technology for the marine finfish aquaculture industry. However, issues such as extreme weather events, poor environmental conditions, interactions with parasites, and conflicts with other coastal users are problematic for surface‐based aquaculture. Submerged cages may reduce many of these problems and commercial interest in their use has increased. However, a broad synthesis of research into the effects of submerged culture on fish is lacking. Here, we review the current status of submerged fish farming worldwide, outline the biological challenges that fish with fundamentally different buoyancy control physiologies face in submerged culture, and discuss production benefits and problems that might arise from submerged fish farming. Our findings suggest that fish with closed swim bladders, and fish without swim bladders, may be well‐suited to submerged culture. However, for fish with open swim bladders, such as salmonids, submergence is more complex as they require access to surface air to refill their swim bladders and maintain buoyancy. Growth and welfare of open swim bladder fish can be compromised by submergence for long periods due to complications with buoyancy regulation, but the recent addition of underwater air domes to submerged cages can alleviate this issue. Despite this advance, a greater understanding of how to couple advantageous environmental conditions with submerged culture to improve fish growth and welfare over the commercial production cycle is required if submerged cages are to become a viable alternative to surface‐based cage aquaculture.